De inventores a ouvintes: o rádio no imaginário científico e tecnológico (1920/1930) - Vieira, Michele Cruz (2010)
This research proposes to investigate the sprouting about a new daily practical brought by the contact of the public, between 1920 and 1930, with the technology of the radio. From the study about the trajectory of the Rádio Sociedade do Rio de Janeiro, first regular broadcasting station of Brazil created in 1923, this work analyzes of that it forms the vehicle was appropriate for a group of literate intellectuals, led for Edgard Roquette-Pinto, all of them followers of the Positivismo, whom they intended to popularize the radio as technology, at the same time that they restricted the contents to an elitist proposal. Accepeted as a new technique, result of a miracle of science, the radio would have to follow an educative-cultural project in search of the progress and the civilization. The people, stimulated for this proposal, started to create an inventive movement of construction of home-made radio equipment, with handmade form and low cost. This know-to make technician, result of the bricolage, was spread quickly in the city of Rio de Janeiro, especially in the suburb, and made to be born an specific public for the radio. Analyzing period magazines, the correspondence of Roquete- Pinto and hundreds of documents in the archive of the Rádio Sociedade do Rio de Janeiro, we also show the way how the dissemination of the technology happened and which were the relation between public and the vehicle during its first decade of existence, that is, at a moment that can be considered the beginning of the radio